Perancangan Foldable Wall-Mounted Workbench Untuk Memudahkan Pekerjaan Tukang Kayu - Kurdi, Ojo (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2021)
Workbench is a device that supports all the projecst of carpenter. Good workbench have to help the Carpenter completed their jobs effectively. Standard workbench has the limitation and it can not help carpenter perfectly. Therefore, it is necessary to redesign the standard workbench in order to enhance its performance. The objective of this aper is to design the workbench that efficient for the small rooms. The design process used the systematic approach where all the stages are related and continuously each others. The first stage of design process is identification problem, continued by the conseptual design, making the decision matrix for the entire alterantive models and the last step is evaluation. The result of the process is the final design that has these criteria, frame-mounted hinge, square hollow steel frame, support components with door mechanism, face vise with large diameter handle. The model has the highest mark compred to others alternative models. Stress analysis of finite element simulation result also shows that the model is safe and it can withstand all the loads during the operation